Effects of increased phosphorus fertilizer on C, N, and P stoichiometry in different organs of bluegrass (Poa L.) at different growth stages - Wang, Jiahao; He, Keyan; Bao, Gensheng; He, Lin; Xu, Hang; Song, Meiqi; Jin, Ling; Wei, Xiaoxing (Frontiers in Ecology and Evolution, 2023)
Introduction The application of phosphorus (P) fertilizer can promote photosynthesis in forage grasses and accelerate their establishment. Methods To improve the utilization efficiency of P fertilizer for bluegrass (Poa L.) in alpine regions, the effects of P fertilizer on their growth, and carbon (C), nitrogen (N) and P distribution in their different organs of them are tested at six P fertilization levels (3, 6, 9, 12, 15, 18 g·m−2). Results (1) The nutrient content in each organ of bluegrass varies during different growth stages, with the lowest nutrient content occurring in the wilt stage. (2) The response of the nutrient content and ratio of each organ of bluegrass to different P fertilization levels varies. When the P application rate was 15 g·m−2, the contents of N and P in roots were the highest, and their C/N and C/P ratios were the lowest. When the P application rate was 12 g·m−2, the contents of N and P in the stems were the highest, and their C/N and C/P ratios were the lowest. When the P application rate was 9 g·m−2, the contents of N and P in leaves were the highest, and their C/N and C/P ratios were the lowest. When the P application rate was 6 g·m−2 the contents of N and P in the panicle were the highest, and their C/N and C/P ratios were the lowest. Discussion These results provide a better understanding of the effect of P fertilization in the nutrient partitioning pattern of perennial forage plant organs in alpine regions. The information from this study can support a more reasonable P fertilization for the establishment of early grassland. For example, in artificial forage grassland, the application of low-concentration P fertilizer (6~9 g·m−2) can promote the nutrient content in spikes and stems of forage grass; for ecological management, the application of high-concentration P fertilizer (15 g·m−2) can promote the nutrient content in roots and enhance the ecological benefits of forage grassland.